A cross-talk EGFR/VEGFR-targeted bispecific nanoprobe for magnetic resonance/near-infrared fluorescence imaging of colorectal cancer. (18th July 2018) - Wang, Qian; Zhao, Xinming; Yan, Hao; Kang, Feiyu; Li, Zhangfu; Qiao, Yanyan; Li, Dan
Abstract: Abstract : Due to the lack of an effective and noninvasive screening tool, the early diagnosis of colorectal cancer (CRC) is currently difficult. For the early diagnosis of CRC, we have developed Fe3 O4 -Dye800-single chain fragment variable (ScFv)egfr/vegfr nanoprobes. ScFvegfr/vegfr (ScFv2 ) conjugated onto Fe3 O4 nanoprobes efficiently recognized CRC tumors in vitro and in vivo. Near-infrared fluorescence imaging modalities such as Dye800 were utilized simultaneously with magnetic resonance to enhance detection efficiency. Fe3 O4 -Dye800-ScFv2 successfully detected tiny CRC tumors; the synergistic ScFv2 successfully enhanced CRC targeting. Thus, Fe3 O4 -Dye800-ScFv2 nanoprobes may represent a new molecular imaging strategy for the early detection of CRC.